2013
DOI: 10.1002/oby.20334
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent weight loss for weight management programs delivered by phone and clinic

Abstract: Objective Face-to-face weight management is costly and presents barriers for individuals seeking treatment; thus, alternate delivery systems are needed. The objective of this study was to compare weight management delivered by face-to-face (FTF) clinic or group conference calls (phone). Design and Methods Randomized equivalency trial in 295 overweight/obese men/women (BMI = 35.1±4.9, Age = 43.8±10.2, Minority = 39.8%). Weight loss (0–6 months) was achieved by reducing energy intake between 1,200– 1,500 kcal/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 35 publications
4
84
1
Order By: Relevance
“…A detailed description of the study design, including inclusion/exclusion criteria, and results for the primary outcomes have been published (10, 15). Briefly, results indicated clinically significant and equivalent weight loss at both 6 and 18 months for the face-to-face (6 mos.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the study design, including inclusion/exclusion criteria, and results for the primary outcomes have been published (10, 15). Briefly, results indicated clinically significant and equivalent weight loss at both 6 and 18 months for the face-to-face (6 mos.…”
Section: Methodsmentioning
confidence: 99%
“…Data from our recently completed 18 month randomized equivalence trial, which compared identical behavioral weight management interventions delivered by traditional face-to-face group meetings or by phone conference calls (10), provided an opportunity to evaluate long-term patterns of weight change and factors associated with weight change patterns in a sample of overweight and obese middle-age adults. Specifically, the objectives of these analyses were to (a) identify patterns of weight change over 18 months, and (b) to assess the association of baseline participant characteristics (age, sex, race/ethnicity, intervention group, household income, self-efficacy for exercise barriers and weight management) and intervention adherence factors (behavioral sessions completed, compliance with the diet and exercise program, weekly data reports completed) with weight change pattern.…”
Section: Introductionmentioning
confidence: 99%
“…We will use behavioral contracts during recruitment and after the intervention has begun to support our retention efforts and to determine the understanding of participants regarding the requirements for study participation. These strategies resulted in a loss to follow-up of 22% in our recently completed trial comparing the effectiveness of phone with face-to-face behavioral clinics for weight management [69]. …”
Section: Methodsmentioning
confidence: 99%
“…Killen, Lauren G et al proved in their study "Live versus DVD exercise in college aged females" published in "Journal of sports and conditioning research" that heart rate and rate of perceived exertion was higher during live session as compared during DVD workout. Also, Joseph E Donnelly in a study "Aerobic exercise alone results in clinically significant weight loss for men and women" [6] published in obesity concluded that exercise at 400 or 600 kcal/session resulted in a significant reduction in weight in weight compared to controls. In group B, weight reduced by 0.73 kilograms (p=0.0004), waist girth reduced by 1.1 centimetres (p<0.0001), and hip girth by 1.16 centimetres (p= 0.0002).…”
Section: Supervised Exercise Versus Workout Videos For Weight Reductimentioning
confidence: 99%